Planning for nodes, places and people in Flanders and Brussels: Developing an empirical railway station assessment model for strategic decision-making - Freke Caset; Filipe Marques Teixeira; Ben Derudder; Kobe Boussauw; Frank Witlox (Journal of Transport and Land Use)
Against the backdrop of current policy discussions in Flanders dealing with differentiated urban development schemes for strategic railway stations, this paper develops an empirical railway station assessment tool. We build on the node-place modeling literature, and more specifically on the tradition of quantitative station assessment models which has emerged from it. First, a series of methodological contributions are proposed in which we suggest strategies to improve the analytical strength of some standard node-place parameters, we broaden the model with temporal variability in accessibility, and we complement the model with a user-based accessibility account. Second, the conceptual model is applied to the case of Flanders and Brussels (the north of Belgium). Drawing on factor and cluster analysis, two intelligible station typologies are produced for both node-place and user-based data. Both typologies are interpreted and complemented with station-specific rose diagrams summarizing a station’s accessibility profile. These diagrams reveal insightful and detailed knowledge about station-specific accessibility characteristics, some of which are not captured by standard node-place analyses. Lastly, a more in-depth discussion focusing on five exemplary cases reveals what the results of these analyses may mean for planning practice.